Bridging the Industry 4.0 Skills Gap: An Immersive Augmented Reality Mobile Learning Approach for Vocational Education - Raimon Efendi; Ambiyar; Estuhono; Ratih Agustin Wulandari (International Journal of Interactive Mobile Technologies (iJIM), 2025)
Vocational high schools encounter substantial challenges in preparing graduates who can meet the demands of the 21st century. This study developed and assessed an innovative mobile learning model based on augmented reality (ARMOL) to enhance vocational students’ competencies, using both the ADDIE model for instructional design and the SEM-PLS method to evaluate effectiveness. The urgency of this research stems from the disparity between vocational graduates’ skills and industry needs, coupled with augmented reality’s (AR) potential to offer a more immersive and interactive learning experience. By employing the ADDIE model, the research successfully created a valid, practical, and effective AR-based mobile learning model. This model enhances students’ cognitive, affective, and psychomotor competencies and fosters 21st-century skills such as critical thinking, creativity, collaboration, and communication. The SEM-PLS analysis revealed significant improvements in creativity and critical thinking, while effects on communication and collaboration were less pronounced. These findings suggest that while the ARMOL model effectively enhances certain competencies, further refinement is needed to fully address all 21st-century skills. This innovative learning model offers a promising solution for elevating the quality of vocational education and preparing graduates for global competition.